2005
DOI: 10.1186/1472-6815-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of the temporal bone – a case report

Abstract: Background: Giant cell tumor is a benign but locally aggressive bone neoplasm which uncommonly involves the skull. The petrous portion of the temporal bone forms a rare location for this tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…1,6,7 On reviewing the available literature, some individual cases were excluded according to the reclassification of giant cell reparative granuloma (GCRG) by Hirschl and Katz in 1974. 8 One hundred and ten GCTs of the skull, including Mayo's series, 10 reviews 3,5,7,[9][10][11][12][13][14][15] and cases reported by otorhinologists, [16][17][18][19][20][21][22][23][24] showed that the sphenoid (52 cases) and temporal bones (40 cases) were the most common sites in the skull. GCTs involving the cranial vault (18 cases) are much rarer, and sometimes occur in association with Paget's disease.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7 On reviewing the available literature, some individual cases were excluded according to the reclassification of giant cell reparative granuloma (GCRG) by Hirschl and Katz in 1974. 8 One hundred and ten GCTs of the skull, including Mayo's series, 10 reviews 3,5,7,[9][10][11][12][13][14][15] and cases reported by otorhinologists, [16][17][18][19][20][21][22][23][24] showed that the sphenoid (52 cases) and temporal bones (40 cases) were the most common sites in the skull. GCTs involving the cranial vault (18 cases) are much rarer, and sometimes occur in association with Paget's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior extensions into the PCF, though rare, can be aggressive and extremely challenging to treat as seen in case 5 of our series. The reports of GCTs by other authors [Cook et al, 1986;Findlay et al, 1987;Rock et al, 1994;Saleh et al, 1994;Silvers et al, 1996;Lee and Lum, 1999;Gibbons et al, 2000;Tang et al, 2003;Pai et al, 2005;Elder et al, 2007;Matsushige et al, 2008;Isaacson et al, 2009;Iizuka et al, 2012] show that most authors achieved radical tumor removal through lateral skull base or neurosurgical procedures with adequate locoregional control ( table 2 ). The facial nerve and the lower cranial nerves were preserved during surgery in all our cases.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Giant cell tumor of bone is a benign lesion that is usually solitary and locally aggressive. 6 Most patients present with slowly progressive pain with or without a mass. Hearing loss, pain and cranial nerve paralysis of the facial nerve are the common presenting complaints.…”
Section: Discussionmentioning
confidence: 99%